PENGARUH CORPOTE SOSISAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN SIZE PERUSAHAAN SEBAGAI PEMODERASI (Studi Kasus Pada Perusahaan Pertambangan Bursa efek Indonesia Periode 2007-2011) - Azib Azib; Ade Sopian (Universitas Islam Bandung, 2013)
ABSTRACT This Purpose resreach to know the influence of Corporate Social Responsibility Perfomance Against Corporate Finance (Return on Asset) By Size Company for Moderation Variables.This study take a sample of Mining Companies listed on the Indonesia Stock Exchange (BEI) in the period 2007 to 2011. The data was colleted using purposive sampling and acquired 6 companies. The method used is descriptive method with approach method verifikatif. The result of this study indicate that Corporate Social Responsibility (CSR) does not have a significant influence on financial performance (Return on Asset) on Mining Companies listed on the Indonesia Stock Exchange (sig. 0,631 > 0.05) with the influence exerted by only 0, 8% By size/ Size of the company proved to act as moderating variable that strengthens the influence of Corporate Social Responsibility (CSR) to the Financial Peformance (ROA) in Ptambangan Company listed in Indonesia Stock Exchange, as demontrasted by the sig. to test the difference in the absolute value of 0,017 which is less than 0,05 (Significant) Keyword : Corporate Social Responsibility, Return on Asset and Size